Penerapan Metode MOOSRA Dalam Seleksi Pengantaran Pemesanan Kue Online Menggunakan Pembobotan ROC - Mohammad Aldinugroho Abdullah; Rima Tamara Aldisa (JURIKOM (Jurnal Riset Komputer), 2023)
Each cake shop certainly has its own website that can be used to order cakes and of course has its own advantages and disadvantages which can be used as an assessment of the quality of the application, such as the types of cakes provided vary at more affordable prices and even the existence of discounted prices makes consumers more interested in ordering cakes online. The large number of these applications makes service users confused about choosing a better application among the good ones, therefore a study was made that discussed techniques for solving these problems using a decision support system. In this study, there are two methods used in the SPK method, including the ROC method which is used as an arrangement of weights of importance on five features that are used as rules which include application usability, Rating Reviews, Promos (Discounts), Cake Menu and Handling Fees. The second method is the Multiobjective Optimization on the Basis of Simple Ratio Analysis (MOOSRA) method which will be used to select 8 online cake ordering applications by ranking each alternative based on predetermined criteria. The final result after applying the two SPK methods is that Akul cake delivery is declared the best online cake delivery application with a preference value of 38.012.